THE ROLE OF WILAYAT AL-HISBAH IN THE IMPLEMENTATION OF ISLAMIC SHARIAH IN ACEH* - Muhammad, Rusjdi Ali (State Islamic University (UIN) Ar-Raniry, 2017)
The Wilayat al-Hisbah (WH), known also as sharia police in Aceh, plays important roles in implementing Islamic law in Aceh - Indonesia. In one hand they must act profesionally based on Islamic principles, unfortunately their future career is still unclear. In national level there are no clear regulations mentioning the WH cjareer path. This consequences lead to the profesionalitiy of WH. Most of them will switch their career to other career having clear future career and also having clear regulation arranging the career.